PERUBAHAN RESPONS RESEPTOR ADRENERGIK-βDAN MUSKARINIK DI OTOT POLOS SALURAN NAFAS TIKUS WISTAR PADA PROSES PENUAAN - Karyono, Setyawati Soeharto (Fakultas Kedokteran Universitas Brawijaya, 2006)
Aging process is a unique and complex process whichcould not be prevented. Many physiologic changes could be seen for adaptation during aging process. These changes influence pharmacodynamic and pharmacokinetic of drug and cause alteration of drug effect. Pharmacodynamic changes are caused by alteration of drug receptor.The objective of this study was to evaluate the influence of aging on β-adrenergic and muscarinic receptors function in rat airway smooth muscle. Isolated tracheal ring preparation and lung strip were used to examine relaxation response to isoprenaline (β-adrenergic agonist) and contraction response to metacholine (muscarinic agonist). Tracheal ring preparations and lung strip were taken from young (4-5 weeks), adult (4-6 months) and old (24-26 months) wistar rats.